"Hot and sticky" and "cold and damp" pyroclastic eruptions, and their relationship with topography: valley- and lake-filling ignimbrites, Ardnamurchan, NW Scotland - Brown, David; Quirie, Ailsa; Reynolds, Peter; Drake, Simon (Volcanica, 2024)
Pyroclastic density currents are complex mixtures of rock, ash and gas and represent significant hazards at many active volcanoes worldwide. Ignimbrites are the deposits of pyroclastic density currents and can be used to record the eruption dynamics and the interaction of the current with the landscape over time and space. The Sròn Mhòr Member in Ardnamurchan, NW Scotland, is a newly documented sequence of silicic Paleocene ignimbrites. Five phases of eruption are recorded by the ignimbrites, which range from non-welded to welded to lava-like. Between each eruption phase, a period of non-deposition occurred, during which rapid erosion and incision took place. The ignimbrites record how pyroclastic density currents of different temperature, grain size, rheology, and composition interacted with the landscape, filling ancient valleys and lakes, before switching to or re-establishing new drainage pathways. Our results provide further insight into ignimbrite deposition that can be applied to volcanoes worldwide.